2010
DOI: 10.1177/0272431609361203
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Risk Behavior Outcomes of Childhood Externalizing Behavioral Trajectories

Abstract: Little is known about the early childhood indicators of adolescent risk. The link between trajectories of externalizing behavioral problems and early adolescent risk behavior was examined in a longitudinal sample of 875 child participants in the LONGSCAN studies. Five trajectory groups of children defined by externalizing behavior problems were identified: Low, Low-Medium, Moderate, Increasing-High, and High. After controlling for demographics and maltreatment, violent/delinquent behavior was significantly pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 45 publications
7
55
1
Order By: Relevance
“…Moreover, as hypothesized, emerging adults were found to report lower levels of anxiety and depression than adolescents, but differently than hypothesized, they did not diverge from teens in the reported levels of externalizing behavioral problems, stress, and feelings of loneliness. The findings concerning the differences seem to corroborate results of previous studies (Thompson et al 2011) showing that adolescence can be considered as a developmental period during which psychological distress is more frequent than the later phases of the life cycle; emerging adulthood may therefore be viewed as a time of improving psychological well-being. In this direction, we found that age differences for some forms of internalizing problems (specifically, anxiety, and depression) are more noticeable in adolescence than in emerging adulthood.…”
Section: Age and Gender Differences In Study Variablessupporting
confidence: 88%
“…Moreover, as hypothesized, emerging adults were found to report lower levels of anxiety and depression than adolescents, but differently than hypothesized, they did not diverge from teens in the reported levels of externalizing behavioral problems, stress, and feelings of loneliness. The findings concerning the differences seem to corroborate results of previous studies (Thompson et al 2011) showing that adolescence can be considered as a developmental period during which psychological distress is more frequent than the later phases of the life cycle; emerging adulthood may therefore be viewed as a time of improving psychological well-being. In this direction, we found that age differences for some forms of internalizing problems (specifically, anxiety, and depression) are more noticeable in adolescence than in emerging adulthood.…”
Section: Age and Gender Differences In Study Variablessupporting
confidence: 88%
“…As noted above, not all previous studies showed this pattern [7, 8]. Importantly, the majority of studies on the topic is based on high-risk samples (bar Moffitt et al and Odgers et al [4, 5]), which opens the possibility that associations between developmental trajectories and problem outcomes are both consequences of (earlier) risk or otherwise confounded and limited in generalizability.…”
Section: Introductionmentioning
confidence: 95%
“…Youth who exhibit externalizing behaviors are at-risk for incarceration, lower graduation rates, and serious mental illness in adolescence and adulthood (Bierman et al, 2013;Brook, Brook, Rubenstone, Zhang, & Sarr, 2011;Thompson et al, 2011). Therefore, there is vast research on factors that contribute to delinquent behaviors, such as NLEs, so that effective prevention and intervention programs can be developed.…”
Section: Negative Life Events and Delinquencymentioning
confidence: 99%